Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Get immediate answers to your questions from a wide network of experienced professionals on our Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
[tex]g(x)=x-3 \ \ \ and\ \ \ h(x)=x^2+6 \\\\(h \circ g) (1)=h\bigg (g(1)\bigg)=h\bigg(1-3\bigg)=h(-2)=(-2)^2+6=4+6=10[/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.